Comparison of transfusion requirements in adult patients undergoing Haploidentical or single‐unit umbilical cord blood stem cell transplantation. (3rd July 2019) - Solves, Pilar; Sanz, Jaime; Gómez, Inés; de la Puerta, Rosalía; Arnao, Mario; Montoro, Juan; Piñana, José Luis; Carretero, Carlos; Balaguer, Aitana; Guerreiro, Manuel; Andreu, Rafa; Rodríguez, Rebeca; et al.
Abstract: Objectives: Umbilical cord blood transplantation (UCBT) and haploidentical hematopoietic stem cell transplantation (haplo‐HSCT) modalities have been developed to offset the lack of matched donors. In this study, we compare the transfusion requirements of patients undergoing UCBT and haplo‐HSCT in a single institution with the aim of providing additional information for clinicians to choose the most adequate alternative graft for HSCT. Methods: The study reviewed 67 and 46 patients undergoing UCBT and haplo‐HSCT, respectively. Results: There were no significant differences for RBC and PLT requirements according to the transplantation modality. Median time to RBC transfusion independence was 35 and 25.5 days in patients who received an UCBT and haplo‐HSCT, respectively ( P = 0.38), while median time to platelet transfusion independence was 31 days for UCBT patients and 23 for haplo‐HSCT patients ( P < 0.001). Days until neutrophils > 0.5 × 10 9 /L were the only variable that significantly influenced RBC and PLT requirements for both transplantation modalities. Cumulative incidence of RBC and PLT transfusion independence at 90 days after transplantation was similar for both UCBT and haplo‐HSCT. Conclusions: Both transplantation platforms require prolonged and intensive supportive RBC and PLT transfusion therapy. Both transplantation platforms require prolonged and intensive supportive RBC and PLT transfusion therapy.